Water jade quick-acting coating liquid as well as preparation method and application thereof

By preparing a water-based quick-acting coating solution composed of mesoporous silica-modified waterborne acrylic resin, nano-strontium titanate, and nano-titanium dioxide, the problems of insufficient stability and mechanical strength of waterborne coating solutions were solved, achieving a high-durability and high-gloss automotive paint protection effect.

CN120842924AInactive Publication Date: 2025-10-28ZHEJIANG LUBAT TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510941122.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-09
Publication Date
2025-10-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing water-based coating solutions have short effective time, insufficient mechanical strength, poor film stability, and high operational requirements, making it difficult to meet the long-term protection needs of automotive paint.

Method used

A water-based quick-acting coating solution, composed of mesoporous silica-modified waterborne acrylic resin, nano-strontium titanate and nano-titanium dioxide, modified corn starch, quantum dot-modified titanium nitride nanocrystals, antibacterial agents and dispersants, is prepared through a specific process to form a protective film with high durability and gloss.

Benefits of technology

It improves the hardness, wear resistance, weather resistance and gloss of the coating, enhances the adhesion between the film and the substrate, has self-cleaning and antibacterial properties, and significantly improves the durability and photothermal stability of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a buffalo quick-acting coating liquid as well as a preparation method and application thereof, and relates to the technical field of automobile parts. The coating liquid is prepared from the following raw materials in parts by weight: 6 to 10 parts of mesoporous silica modified waterborne acrylic resin, 1 to 2 parts of nano strontium titanate, 3 to 4 parts of nano titanium dioxide, 3 to 6 parts of modified corn starch, 1 to 2 parts of quantum dot modified titanium nitride nanocrystals, 1 to 2 parts of antibacterial agent, 0.5 to 1 part of dispersing agent, 80 to 100 parts of deionized water and 2 to 4 parts of polyglycerol ester. The coating liquid provided by the invention has the advantages of high coating speed, good coating effect, good durability and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of automotive parts technology, and in particular to a water-based quick-acting coating liquid, its preparation method and application. Background Technology

[0002] During car use, owners are paying increasing attention to vehicle maintenance, including not only interior cleaning and upkeep but also exterior paint care. However, over time, fine scratches gradually appear on the metallic paint surface, leading to reduced shine and a loss of luster. This is exacerbated by the friction from dust during frequent car washes and sweepings. Currently, paint detailing and maintenance products on the market are mainly divided into three categories: waxes, glazes, and coatings.

[0003] Automotive coating liquid is a high-performance car care product specifically designed for automotive paint, glass, and interior surfaces. It provides comprehensive protection by forming a uniform, transparent, and robust protective film. Traditional oil-based coating methods are time-consuming and require absolute dust control; otherwise, the coating will be uneven, with dust trapped within the polymer film affecting aesthetics. Therefore, extremely high precision is required; even slight errors can result in uneven coatings and surfaces. Recently, water-based coating liquids have emerged on the market. Using water as a solvent, they contain little to no organic solvents, significantly reducing VOC emissions and meeting environmental requirements. They are environmentally friendly, and the application process is relatively simple, requiring no complex equipment or processes. Multiple application methods, such as spraying and brushing, are suitable for various substrates. However, existing water-based coating liquid products still suffer from problems such as short effective time, insufficient mechanical strength, and poor film stability. Summary of the Invention

[0004] In order to provide an aqueous coating solution that has fast coating speed, good coating effect and strong durability, this application provides a water-based quick-acting coating solution, its preparation method and application.

[0005] This application provides a water-based fast-acting coating solution, which adopts the following technical solution:

[0006] A water-based quick-acting coating solution, the raw materials by weight are as follows: 6-10 parts of mesoporous silica-modified waterborne acrylic resin, 1-2 parts of nano-strontium titanate, 3-4 parts of nano-titanium dioxide, 3-6 parts of modified corn starch, 1-2 parts of quantum dot-modified titanium nitride nanocrystals, 1-2 parts of antibacterial agent, 0.5-1 part of dispersant, 80-100 parts of deionized water, and 2-4 parts of polyglycerol ester.

[0007] Preferably, the raw materials include, by weight, 8 parts of mesoporous silica-modified waterborne acrylic resin, 1.5 parts of nano-strontium titanate, 3.5 parts of nano-titanium dioxide, 4.5 parts of modified corn starch, 1.5 parts of quantum dot-modified titanium nitride nanocrystals, 1.5 parts of antibacterial agent, 0.8 parts of dispersant, 90 parts of deionized water, and 3 parts of polyglycerol ester.

[0008] Preferably, the modified corn starch raw material includes sodium hypochlorite oxidized hydroxypropyl corn starch, C 12 -C 14 Alkyl glycidyl ether; the mass ratio of sodium hypochlorite oxidized hydroxypropyl corn starch to C12-C14 alkyl glycidyl ether is 1:0.25-0.35.

[0009] Preferably, the sodium hypochlorite oxidized hydroxypropyl corn starch raw material comprises, by weight, 10 parts corn starch, 9-10 parts ethanol, 1-1.1 parts water, 3.4-4.5 parts sodium hypochlorite, 3-3.4 parts sodium hydroxide solution, and 3.5-4.5 parts propylene oxide.

[0010] Preferably, the method for preparing sodium hypochlorite-oxidized hydroxypropyl corn starch includes the following steps:

[0011] Corn starch was added to a mixed solution of ethanol and distilled water and stirred to form a homogeneous corn starch emulsion. The emulsion was then heated to 40-60°C in a water bath, and the pH of the emulsion was adjusted to 8-9. Sodium hypochlorite was added to initiate the reaction, and the pH of the emulsion was maintained at 8-9. After the reaction was completed, the temperature was raised to 50-60°C, sodium hydroxide solution was added, nitrogen gas was introduced, and propylene oxide was added. After reacting for 16-20 hours, the pH of the emulsion was adjusted to 6-7 to stop the reaction. After the reaction was completed, the emulsion was filtered, washed several times, dried, pulverized, and sieved to obtain sodium hypochlorite-oxidized hydroxypropyl corn starch.

[0012] Preferably, the method for preparing the modified corn starch includes the following steps:

[0013] C 12 -C 14 After alkyl glycidyl ether and sodium hypochlorite oxidized hydroxypropyl corn starch are mixed evenly, the mixture is then placed in a high-pressure reactor, heated to 120-140℃, and allowed to stand for 100-120 hours. After the reaction is completed, the starch is dispersed with distilled water, filtered, and the filter cake is washed and dried at 45-50℃ for 12-16 hours. Then, it is pulverized and sieved to obtain the modified starch.

[0014] Preferably, the quantum dot-modified titanium nitride nanocrystal raw material comprises, by weight: 0.01-0.02 parts graphene quantum dots, 50-100 parts ultrapure water, and 1-2 parts nano-titanium nitride.

[0015] Preferably, the preparation method of the quantum dot-modified titanium nitride nanocrystals includes the following steps:

[0016] Graphene quantum dots were dispersed in ultrapure water, and then nano-titanium nitride was added. After stirring evenly, a mixture was obtained. The mixture was placed in a hydrothermal reactor and transferred to a drying oven. It was kept at 180-200℃ for 6-10 hours, cooled to room temperature, centrifuged and washed several times, and finally dried in a drying oven at 60-70℃ for 24-30 hours to obtain quantum dot-modified titanium nitride nanocrystals.

[0017] This application provides a method for preparing a water-based quick-acting coating solution, which adopts the following technical solution:

[0018] A method for preparing a water-based quick-acting coating solution includes the following steps:

[0019] S1. Heat 40-50 parts of deionized water to 50-60℃, add 1-2 parts of nano-strontium titanate, 3-4 parts of nano-titanium dioxide and 1-2 parts of quantum dot modified titanium nitride nanocrystals, then add 0.5-1 parts of dispersant, stir at 800-1000 rpm for 20-30 min, and then ultrasonically disperse for 20-30 min to obtain a nano-dispersion;

[0020] S2. Heat 40-50 parts of deionized water to 50-70℃, add 6-10 parts of mesoporous silica-modified waterborne acrylic resin, and stir at 500-600 rpm until completely dissolved to obtain a resin solution; slowly add the nano-dispersion dropwise to the resin solution, and after the dropwise addition is complete, add 3-6 parts of modified corn starch, heat to 60-70℃ and continue stirring for 40-50 minutes;

[0021] S3. After cooling to room temperature, add 2-4 parts of polyglycerol ester and 1-2 parts of antibacterial agent in sequence, and stir at 200-300 rpm for 20-30 minutes to obtain the water turquoise fast-acting coating solution.

[0022] The application of the water-based quick-acting coating solution provided in this application adopts the following technical solution:

[0023] An application of a water-based quick-acting coating liquid, wherein the water-based quick-acting coating liquid is used in automotive paint surfaces and automotive interiors.

[0024] In summary, this application includes at least one of the following beneficial technical effects:

[0025] 1. This application uses mesoporous silica-modified waterborne acrylic resin as a matrix. The mesoporous silica-modified waterborne acrylic resin has good mechanical strength and durability, and the hardness and wear resistance of the coating are significantly improved after modification with mesoporous silica, while also having good waterborne dispersion performance. Nano-strontium titanate and nano-titanium dioxide have excellent weather resistance and UV resistance, which can effectively prevent surface aging and maintain long-term gloss and transparency. Quantum dot-modified titanium nitride nanocrystals can improve the optical properties of the coating, enhance reflectivity and gloss, and also effectively enhance the hardness of the coating. Polyglycerol ester can provide good adhesion to the coating surface, enhance the adhesion between the film layer and the substrate, and ensure the stability and durability of the coating.

[0026] 2. The modified corn starch provided in this application is first oxidized with sodium hypochlorite, then hydroxypropyl etherified, and then further subjected to C... 12 -C 14 Hydrophobic etherification of alkyl glycidyl ethers produces a modified corn starch with a balance of hydrophilicity and hydrophobicity. This modified starch not only has good dispersibility and mechanical properties, but also self-cleaning and antibacterial properties, which can effectively improve the self-cleaning and stain resistance of coatings.

[0027] 3. This application uses a hydrothermal reaction method to composite graphene quantum dots onto the surface of nano-titanium nitride. The resulting quantum dot-modified titanium nitride nanocrystals have excellent fluorescence properties, effectively improving the reflectivity, gloss, and protective effect of the coating. It can also effectively improve the hardness of the coating, enhance the photothermal stability of the coating, and significantly improve the durability of the coating. Detailed Implementation

[0028] The present application will be further described in detail below with reference to the embodiments.

[0029] The chemical reagents used in the preparation examples, embodiments, and comparative examples provided in this invention are all commercially available products, and their brands and manufacturers are as follows:

[0030] Graphene quantum dots, Shanghai Aladdin Biochemical Technology Co., Ltd., Product No.: G196610;

[0031] Nano-titanium nitride, Shanghai Maclean Biochemical Technology Co., Ltd., T819470;

[0032] Decaglycerol monolaurate, Wuhan Xinyang Ruihe Chemical Technology Co., Ltd.;

[0033] Nano silver antibacterial agent, Foshan Lanfeng Additives Co., Ltd.;

[0034] C 12 -C 14 Alkyl glycidyl ethers, Hubei Zhenbo Chemical Co., Ltd.;

[0035] Corn starch, Shanghai Yi'en Chemical Technology Co., Ltd.;

[0036] Propylene oxide, Jiangsu Puleisi Biotechnology Co., Ltd.;

[0037] Strontium titanate nanomaterials, Shanghai Maclean Biochemical Technology Co., Ltd., S818365;

[0038] Nano titanium dioxide, Shanghai Maclean Biochemical Technology Co., Ltd., T818939;

[0039] Water-based sodium polyacrylate dispersant, Nantong Hantai Chemical Co., Ltd.

[0040] Preparation Example 1: Preparation of Mesoporous Silica-Modified Waterborne Acrylic Resin

[0041] S1. Measure 100 mL of deionized water, add 0.347 g of triethanolamine and 1.2 g of hexadecyltrimethylammonium bromide in sequence, stir and disperse for 20 min, then heat to 60 °C with magnetic stirring; add 14.58 g of tetraethyl orthosilicate, continue stirring and heating to 75 °C, react for 2 h and discharge, filter to obtain crude product; wash the crude product with water and centrifuge twice, wash with ethanol and centrifuge three times, then dry the product in an oven at 100 °C for 24 h; calcine the dried product in a muffle furnace at 600 °C for 5 h, then cool to room temperature and grind into powder to obtain mesoporous silica nanoparticles;

[0042] S2. 0.3 g of mesoporous silica nanoparticles were added to 20 mL of N,N-dimethyldiformamide and ultrasonically dispersed for 30 min to obtain a uniform mesoporous silica nanoparticle dispersion. The mesoporous silica nanoparticle dispersion was stirred in a nitrogen atmosphere and heated to 50 °C. 5.6 g of isophorone diisocyanate was added to 10 mL of N,N-dimethyldiformamide for dilution, and then 2 drops of stannous isooctanoate were added and slowly added dropwise to the mesoporous silica nanoparticle dispersion. The mixture was heated to 70 °C and reacted for 4 h, then cooled to 50 °C. A mixed solution of 20 mL of N,N-dimethyldiformamide and 5.8 g of hydroxyethyl methacrylate was added, and the mixture was heated to 70 °C and reacted at a constant temperature for 8 h. After the reaction was completed, the mixture was cooled to room temperature. The mixture was washed with methanol, filtered several times, washed five times with deionized water and filtered again, and then dried in a vacuum drying oven at 30 °C for 24 h. After thorough grinding, ethylene-modified mesoporous silica nanoparticles were obtained.

[0043] S3. Weigh 0.46g of ethylene-modified mesoporous silica nanoparticles and add them to 5mL of isopropanol solvent for ultrasonic dispersion for 10min. Weigh 5.00g of hydroxyethyl methacrylate, 5.80g of acrylic acid, 20.0g of methyl methacrylate, 12.9g of butyl acrylate, 2.20g of isoborneol methacrylate, and 0.80g of azobisisobutyronitrile. Mix them evenly at room temperature to obtain a mixed solution. Add 1 / 3 of the mixed solution directly to 70mL of isopropanol solvent heated to 50℃. Stir evenly and heat to 70℃. Add the remaining 2 / 3 of the mixed solution dropwise over 2h. After the dropwise addition is complete, react at a constant temperature for 4h. Cool to 50℃ and add triethylamine for neutralization. When the pH is 7-8, remove the solvent from the reaction system. Add deionized water and emulsify for 0.5h to obtain mesoporous silica-modified waterborne acrylic resin.

[0044] Preparation Example 2: Preparation of Modified Corn Starch

[0045] Preparation Example 2.1

[0046] S1. Add 10g of corn starch to a mixed solution of 9g ethanol and 1g water, stir to form a uniform corn starch emulsion, then heat to 40℃ in a water bath and adjust the pH of the starch emulsion to 8; add 3.4g of sodium hypochlorite to start the reaction for 3h, and maintain the pH of the starch emulsion at 8; after the reaction is complete, raise the temperature to 50℃, then add 3g of 50% sodium hydroxide solution and purge with nitrogen gas, add 3.5g of propylene oxide, and start the reaction for 16h. Then adjust the pH of the starch emulsion to 6 to stop the reaction; after the reaction is complete, filter the starch emulsion and wash it 3 times with ethanol, dry it, pulverize it and pass it through a 100-mesh sieve to obtain sodium hypochlorite oxidized hydroxypropyl corn starch;

[0047] S2. Add 2.5g of C 12 -C 14 Alkyl glycidyl ether was mixed evenly with 10g of sodium hypochlorite-oxidized hydroxypropyl corn starch prepared from S1, and then loaded into a high-pressure reactor. The mixture was heated to 120℃ and allowed to stand for 100h. After the reaction was completed, the starch was dispersed with distilled water, filtered, and the filter cake was washed with distilled water, 50%, 75% and anhydrous ethanol, dried at 50℃ for 12h, pulverized and passed through a 100-mesh sieve to obtain modified starch.

[0048] Preparation Example 2.2

[0049] S1. Add 10g of corn starch to a mixed solution of 9.5g of ethanol and 1.05g of water, stir to form a uniform corn starch emulsion, then heat to 50℃ in a water bath and adjust the pH of the starch emulsion to 8.5; add 4g of sodium hypochlorite to start the reaction for 4h, and maintain the pH of the starch emulsion at 8.5; after the reaction is complete, raise the temperature to 55℃, then add 3.2g of 50% sodium hydroxide solution and purge with nitrogen gas, add 4g of propylene oxide, and start the reaction for 18h. Then adjust the pH of the starch emulsion to 6.5 to stop the reaction; after the reaction is complete, filter the starch emulsion and wash it three times with ethanol, dry it, pulverize it, and pass it through a 100-mesh sieve to obtain sodium hypochlorite-oxidized hydroxypropyl corn starch;

[0050] S2. Add 3g C 12 -C 14 Alkyl glycidyl ether was mixed evenly with 10g of sodium hypochlorite-oxidized hydroxypropyl corn starch prepared from S1, and then loaded into a high-pressure reactor. The mixture was heated to 130℃ and allowed to stand for 110h. After the reaction was completed, the starch was dispersed with distilled water, filtered, and the filter cake was washed with distilled water, 50%, 75% and anhydrous ethanol, dried at 50℃ for 14h, pulverized and passed through a 100-mesh sieve to obtain modified starch.

[0051] Preparation Example 2.3

[0052] S1. Add 10g of corn starch to a mixed solution of 10g of ethanol and 1.1g of water, stir to form a uniform corn starch emulsion, then heat to 60℃ in a water bath and adjust the pH of the starch emulsion to 9; add 4.5g of sodium hypochlorite to start the reaction for 5h, and maintain the pH of the starch emulsion at 9; after the reaction is complete, raise the temperature to 60℃, then add 3.4g of 50% sodium hydroxide solution and purge with nitrogen gas, add 4.5g of propylene oxide, and start the reaction for 20h. Then adjust the pH of the starch emulsion to 7 to stop the reaction; after the reaction is complete, filter the starch emulsion and wash it three times with ethanol, dry it, pulverize it, and pass it through a 100-mesh sieve to obtain sodium hypochlorite-oxidized hydroxypropyl corn starch;

[0053] S2. Add 3.5g of C 12 -C 14 Alkyl glycidyl ether was mixed evenly with 10g of sodium hypochlorite-oxidized hydroxypropyl corn starch prepared from S1, and then loaded into a high-pressure reactor. The mixture was heated to 140℃ and allowed to stand for 120h. After the reaction was completed, the starch was dispersed with distilled water, filtered, and the filter cake was washed with distilled water, 50%, 75% and anhydrous ethanol, dried at 50℃ for 12h, pulverized and passed through a 100-mesh sieve to obtain modified starch.

[0054] Preparation Example 2.4

[0055] S1. Add 10g of corn starch to a mixed solution of 9g of ethanol and 10g of water, stir to form a uniform corn starch emulsion, then heat to 40℃ in a water bath and adjust the pH of the starch emulsion to 8; add 3.4g of sodium hypochlorite to start the reaction for 3h, and maintain the pH of the starch emulsion at 8; after the reaction is complete, raise the temperature to 50℃, then add 3g of 50% sodium hydroxide solution and purge with nitrogen, add 3.5g of propylene oxide, and start the reaction for 16h. Then adjust the pH of the starch emulsion to 6 to stop the reaction; after the reaction is complete, filter the starch emulsion and wash it 3 times with ethanol, dry it, pulverize it and pass it through a 100-mesh sieve to obtain sodium hypochlorite-oxidized hydroxypropyl corn starch.

[0056] Preparation Example 3: Preparation of quantum dot-modified titanium nitride nanocrystals

[0057] Preparation Example 3.1

[0058] 0.01g of graphene quantum dots were dispersed in 50g of ultrapure water, followed by the addition of 1g of nano-titanium nitride. After stirring evenly, a mixture was obtained. The mixture was placed in a hydrothermal reactor and transferred to a drying oven. It was kept at 180℃ for 6h, cooled to room temperature, centrifuged and washed several times, and finally dried in a drying oven at 60℃ for 24h to obtain quantum dot-modified titanium nitride nanocrystals.

[0059] Preparation Example 3.2

[0060] 0.015g of graphene quantum dots were dispersed in 75g of ultrapure water, followed by the addition of 1.5g of nano-titanium nitride. After stirring evenly, a mixture was obtained. The mixture was placed in a hydrothermal reactor and transferred to a drying oven. It was kept at 190℃ for 8 hours, cooled to room temperature, centrifuged and washed several times, and finally dried in a drying oven at 65℃ for 27 hours to obtain quantum dot-modified titanium nitride nanocrystals.

[0061] Preparation Example 3.3

[0062] 0.02g of graphene quantum dots were dispersed in 100g of ultrapure water, followed by the addition of 2g of nano-titanium nitride. After stirring evenly, a mixture was obtained. The mixture was placed in a hydrothermal reactor and transferred to a drying oven. It was kept at 200℃ for 10h, cooled to room temperature, centrifuged and washed several times, and finally dried in a drying oven at 70℃ for 30h to obtain quantum dot-modified titanium nitride nanocrystals.

[0063] Example 1

[0064] S1. After heating 40g of deionized water to 50°C, add 1g of nano-strontium titanate, 3g of nano-titanium dioxide and 1g of quantum dot-modified titanium nitride nanocrystals prepared in Preparation Example 3.1, then add 0.5g of dispersant, stir at 800rpm for 20min, and then ultrasonically disperse for 20min to obtain a nano-dispersion.

[0065] S2. Heat 40g of deionized water to 50°C, add 6g of mesoporous silica-modified waterborne acrylic resin prepared in Preparation Example 1, and stir at 500rpm until completely dissolved to obtain a resin solution; slowly add the nano-dispersion dropwise to the resin solution, and after the dropwise addition is complete, add 3g of modified corn starch prepared in Preparation Example 2.1, heat to 60°C and continue stirring for 40min;

[0066] S3. After cooling to room temperature, add 2g of polyglycerol ester and 1g of antibacterial agent in sequence, and stir at 200rpm for 20min to obtain the water turquoise fast-acting coating solution.

[0067] The antibacterial agent used in this embodiment is nano-silver antibacterial agent; the polyglycerol ester used is deca-polyglycerol monolaurate; and the dispersant used is water-based sodium polyacrylate dispersant.

[0068] Example 2

[0069] S1. After heating 45g of deionized water to 50°C, add 1.5g of nano-strontium titanate, 3.5g of nano-titanium dioxide and 1.5g of quantum dot-modified titanium nitride nanocrystals prepared in Preparation Example 3.1, then add 0.8g of dispersant, stir at 800rpm for 20min, and then ultrasonically disperse for 20min to obtain a nano-dispersion.

[0070] S2. Heat 45g of deionized water to 50°C, add 8g of mesoporous silica-modified waterborne acrylic resin prepared in Preparation Example 1, and stir at 500rpm until completely dissolved to obtain a resin solution; slowly add the nano-dispersion dropwise to the resin solution, and after the dropwise addition is complete, add 4.5g of modified corn starch prepared in Preparation Example 2.1, heat to 60°C and continue stirring for 40min;

[0071] S3. After cooling to room temperature, add 3g of polyglycerol ester and 1.5g of antibacterial agent in sequence, and stir at 200rpm for 20min to obtain the water turquoise fast-acting coating solution.

[0072] The antibacterial agent used in this embodiment is nano-silver antibacterial agent; the polyglycerol ester used is deca-polyglycerol monolaurate; and the dispersant used is water-based sodium polyacrylate dispersant.

[0073] Example 3

[0074] S1. Heat 50g of deionized water to 50°C, add 2g of nano-strontium titanate, 4g of nano-titanium dioxide and 2g of quantum dot-modified titanium nitride nanocrystals prepared in Preparation Example 3.1, then add 1g of dispersant, stir at 800rpm for 20min, and then ultrasonically disperse for 20min to obtain a nano-dispersion.

[0075] S2. Heat 50g of deionized water to 50°C, add 10g of mesoporous silica-modified waterborne acrylic resin prepared in Preparation Example 1, and stir at 500rpm until completely dissolved to obtain a resin solution; slowly add the nano-dispersion dropwise to the resin solution, and after the dropwise addition is complete, add 6g of modified corn starch prepared in Preparation Example 2.1, heat to 60°C and continue stirring for 40min;

[0076] S3. After cooling to room temperature, add 4g of polyglycerol ester and 2g of antibacterial agent in sequence, and stir at 200rpm for 20min to obtain the water turquoise fast-acting coating solution.

[0077] The antibacterial agent used in this embodiment is nano-silver antibacterial agent; the polyglycerol ester used is deca-polyglycerol monolaurate; and the dispersant used is water-based sodium polyacrylate dispersant.

[0078] Example 4

[0079] S1. After heating 40g of deionized water to 55°C, add 1g of nano-strontium titanate, 3g of nano-titanium dioxide and 1g of quantum dot-modified titanium nitride nanocrystals prepared in Preparation Example 3.1, then add 0.5g of dispersant, stir at 900rpm for 25min, and then ultrasonically disperse for 25min to obtain a nano-dispersion.

[0080] S2. Heat 40g of deionized water to 60°C, add 6g of mesoporous silica-modified waterborne acrylic resin prepared in Preparation Example 1, and stir at 550rpm until completely dissolved to obtain a resin solution; slowly add the nano-dispersion dropwise to the resin solution, and after the dropwise addition is complete, add 3g of modified corn starch prepared in Preparation Example 2.1, heat to 65°C and continue stirring for 45min;

[0081] S3. After cooling to room temperature, add 2g of polyglycerol ester and 1g of antibacterial agent in sequence, and stir at 250rpm for 25min to obtain the water turquoise fast-acting coating solution.

[0082] The antibacterial agent used in this embodiment is nano-silver antibacterial agent; the polyglycerol ester used is deca-polyglycerol monolaurate; and the dispersant used is water-based sodium polyacrylate dispersant.

[0083] Example 5

[0084] S1. After heating 40g of deionized water to 60°C, add 1g of nano-strontium titanate, 3g of nano-titanium dioxide and 1g of quantum dot-modified titanium nitride nanocrystals prepared in Preparation Example 3.1, then add 0.5g of dispersant, stir at 1000rpm for 30min, and then ultrasonically disperse for 30min to obtain a nano-dispersion.

[0085] S2. Heat 40g of deionized water to 50°C, add 6g of mesoporous silica-modified waterborne acrylic resin prepared in Preparation Example 1, and stir at 600rpm until completely dissolved to obtain a resin solution; slowly add the nano-dispersion dropwise to the resin solution, and after the dropwise addition is complete, add 3g of modified corn starch prepared in Preparation Example 2.1, heat to 70°C and continue stirring for 50min;

[0086] S3. After cooling to room temperature, add 2g of polyglycerol ester and 1g of antibacterial agent in sequence, and stir at 300rpm for 30min to obtain the water turquoise fast-acting coating solution.

[0087] The antibacterial agent used in this embodiment is nano-silver antibacterial agent; the polyglycerol ester used is deca-polyglycerol monolaurate; and the dispersant used is water-based sodium polyacrylate dispersant.

[0088] Example 6

[0089] The technical difference between Example 6 and Example 1 is that the modified corn starch used in Example 6 was prepared from Example 2.2.

[0090] Example 7

[0091] The technical difference between Example 7 and Example 1 is that the modified corn starch used in Example 7 was prepared from Example 2.3.

[0092] Example 8

[0093] The technical difference between Example 8 and Example 1 is that the modified corn starch used in Example 8 was prepared from Example 2.4.

[0094] Example 9

[0095] The difference between Example 9 and Example 1 is that the quantum dot-modified titanium nitride nanocrystals used in Example 9 were prepared in Example 3.2.

[0096] Example 10

[0097] The difference between Example 10 and Example 1 is that the quantum dot modified titanium nitride nanocrystals used in Example 10 were prepared in Example 3.3.

[0098] Comparative Example 1

[0099] The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, an equal amount of ordinary unmodified waterborne acrylic resin is used instead of mesoporous silica-modified waterborne acrylic resin.

[0100] Comparative Example 2

[0101] The difference between Comparative Example 2 and Example 1 is that no nano-strontium titanate was added in Comparative Example 2.

[0102] Comparative Example 3

[0103] The technical difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, an equal amount of ordinary unmodified corn starch was used instead of modified corn starch.

[0104] Comparative Example 4

[0105] The difference between Comparative Example 4 and Example 1 is that in Comparative Example 4, an equal amount of ordinary untreated titanium nitride nanocrystals was used instead of quantum dot-modified titanium nitride nanocrystals.

[0106] Performance testing

[0107] The coating solutions obtained in Examples 1-10 and Comparative Examples 1-4 were used to coat the paint of 10 vehicles of the same model, and the following tests were conducted:

[0108] 1. Appearance: Observe whether there are defects such as pits, pinholes, and bubbles in the coating.

[0109] II. Hardness: The pencil hardness of the coating was determined according to GB / T 6739-2022 "Determination of Hardness of Paints and Varnishes by Pencil Method", with a load of 750g. The results are shown in Table 1.

[0110] III. 3M Tape Stain Resistance Test: A rapid test was conducted using 3M Scotch 610-1PK tape. The test method involved laying the 3M tape flat on the film surface, pressing it firmly, and then tearing the tape at a 90° angle perpendicular to the film surface. The residual film surface marks were graded from 1 to 5, with 1 indicating no marks, 2 indicating very slight marks, 3 indicating noticeable marks, 4 indicating residual bright white marks, and 5 indicating delamination. The higher the grade, the worse the stain resistance. The results are shown in Table 1.

[0111] IV. Gloss: The gloss of the coating at 60° was determined with reference to GB / T 9754-2007 "Determination of specular gloss at 20°, 60° and 85° for paints and varnishes without metallic pigments". The results are shown in Table 1.

[0112] V. Artificial Accelerated Aging Test: Refer to GB / T 1865-2009 Paints and Varnishes Artificial Climate Aging and Artificial Radiation Exposure to Filtered Xenon Arc Radiation to conduct an aging test of 1000h on the coating, and determine the gloss retention rate and whether defects such as cracking, chalking, and blistering occur.

[0113] The specific test results are as follows:

[0114] Table 1 Performance Test Results

[0115]

[0116]

[0117] As can be seen from the test results in Table 1, the water-based quick-acting coating solution provided in this application has a smooth and defect-free appearance after coating, a hardness of up to 9H, and passes the 3M tape stain resistance test with a test level of 1, indicating that it has good stain resistance, high gloss, and good aging resistance.

[0118] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed, but as long as they are within the scope of the claims of the present application, they are protected by the patent law.

Claims

1. A water-based fast-acting coating solution, characterized in that: The raw materials, by weight, include 6-10 parts of mesoporous silica-modified waterborne acrylic resin, 1-2 parts of nano-strontium titanate, 3-4 parts of nano-titanium dioxide, 3-6 parts of modified corn starch, 1-2 parts of quantum dot-modified titanium nitride nanocrystals, 1-2 parts of antibacterial agent, 0.5-1 part of dispersant, 80-100 parts of deionized water, and 2-4 parts of polyglycerol ester.

2. The water-based fast-acting coating solution according to claim 1, characterized in that: The raw materials, by weight, include 8 parts of mesoporous silica-modified waterborne acrylic resin, 1.5 parts of nano-strontium titanate, 3.5 parts of nano-titanium dioxide, 4.5 parts of modified corn starch, 1.5 parts of quantum dot-modified titanium nitride nanocrystals, 1.5 parts of antibacterial agent, 0.8 parts of dispersant, 90 parts of deionized water, and 3 parts of polyglycerol ester.

3. The water-based fast-acting coating solution according to claim 1 or 2, characterized in that: The modified corn starch raw material includes sodium hypochlorite oxidized hydroxypropyl corn starch, C 12 -C 14 Alkyl glycidyl ether; sodium hypochlorite oxidized hydroxypropyl corn starch, C 12 -C 14 The mass ratio of alkyl glycidyl ethers is 1:0.25-0.

35.

4. The water-based quick-acting coating solution according to claim 3, characterized in that: The sodium hypochlorite oxidized hydroxypropyl corn starch raw material comprises, by weight, 10 parts corn starch, 9-10 parts ethanol, 1-1.1 parts water, 3.4-4.5 parts sodium hypochlorite, 3-3.4 parts sodium hydroxide solution, and 3.5-4.5 parts propylene oxide.

5. The water-based quick-acting coating solution according to claim 4, characterized in that: The method for preparing sodium hypochlorite-oxidized hydroxypropyl corn starch includes the following steps: Corn starch was added to a mixed solution of ethanol and water and stirred to form a homogeneous corn starch emulsion. The emulsion was then heated to 40-60°C in a water bath, and the pH of the emulsion was adjusted to 8-9. Sodium hypochlorite was added to initiate the reaction, and the pH of the emulsion was maintained at 8-9. After the reaction was completed, the temperature was raised to 50-60°C, sodium hydroxide solution was added, nitrogen gas was introduced, and propylene oxide was added. After reacting for 16-20 hours, the pH of the emulsion was adjusted to 6-7 to stop the reaction. After the reaction was completed, the emulsion was filtered, washed several times, dried, pulverized, and sieved to obtain sodium hypochlorite-oxidized hydroxypropyl corn starch.

6. The water-based quick-acting coating solution according to claim 3, characterized in that: The method for preparing the modified corn starch includes the following steps: C 12 -C 14 After alkyl glycidyl ether and sodium hypochlorite oxidized hydroxypropyl corn starch are mixed evenly, the mixture is then placed in a high-pressure reactor, heated to 120-140℃, and allowed to stand for 100-120 hours. After the reaction is completed, the starch is dispersed with distilled water, filtered, and the filter cake is washed and dried at 45-50℃ for 12-16 hours. Then, it is pulverized and sieved to obtain the modified starch.

7. A quick-acting polka dot coating solution according to claim 1 or 2, characterized in that: The quantum dot-modified titanium nitride nanocrystal raw material comprises, by weight: 0.01-0.02 parts graphene quantum dots, 50-100 parts ultrapure water, and 1-2 parts nano-titanium nitride.

8. The water-based quick-acting coating solution according to claim 7, characterized in that: The method for preparing quantum dot-modified titanium nitride nanocrystals includes the following steps: Graphene quantum dots were dispersed in ultrapure water, and then nano-titanium nitride was added. After stirring evenly, a mixture was obtained. The mixture was placed in a hydrothermal reactor and transferred to a drying oven. It was kept at 180-200℃ for 6-10 hours, cooled to room temperature, centrifuged and washed several times, and finally dried in a drying oven at 60-70℃ for 24-30 hours to obtain quantum dot-modified titanium nitride nanocrystals.

9. A method for preparing a water-based quick-acting coating solution according to any one of claims 1-8, characterized in that: Includes the following steps: S1. Heat 40-50 parts of deionized water to 50-60℃, add 1-2 parts of nano-strontium titanate, 3-4 parts of nano-titanium dioxide and 1-2 parts of quantum dot modified titanium nitride nanocrystals, then add 0.5-1 parts of dispersant, stir at 800-1000 rpm for 20-30 min, and then ultrasonically disperse for 20-30 min to obtain a nano-dispersion; S2. Heat 40-50 parts of deionized water to 50-70℃, add 6-10 parts of mesoporous silica-modified waterborne acrylic resin, and stir at 500-600 rpm until completely dissolved to obtain a resin solution; slowly add the nano-dispersion dropwise to the resin solution, and after the dropwise addition is complete, add 3-6 parts of modified corn starch, heat to 60-70℃ and continue stirring for 40-50 minutes; S3. After cooling to room temperature, add 2-4 parts of polyglycerol ester and 1-2 parts of antibacterial agent in sequence, and stir at 200-300 rpm for 20-30 minutes to obtain the water turquoise fast-acting coating solution.

10. The application of the water-based quick-acting coating solution according to any one of claims 1-8, characterized in that: Application of the water-based quick-acting coating liquid in automotive paint and automotive interiors.